Mandarin irrigation scheduling by means of frequency domain reflectometry soil moisture monitoring - Jiménez-Bello, Miguel Ángel; Lidón, Antonio; Manzano-Juárez, Juan; Badal, Eduardo; Pérez-Pérez, Juan G.; Bonet, Luis; Intrigliolo, Diego S.; Esteban, Alba (Elsevier, 2020)
The accurate estimation of plant water needs is the first step for achieving high crop water productivity. The main objective of the work was to develop an irrigation scheduling procedure for mandarin orchards under Mediterranean conditions based on replacing the amount of consumed water using reference values of soil moisture according to different phenological periods. The proposed methodology includes a definition part where the threshold values were established relating the trees’ stem water potential and the volumetric soil water content measured with Frequency Domain Reflectometry probes. A second part includes the steps for standardizing measurements from capacitance probes by using the LEACHM hydrological simulation model to take into account the sensor-to-sensor variations. Finally, an extrapolation procedure based on soil water retention curves was used for adapting critical soil water content thresholds to different soil conditions. Field evaluations were made in a citrus orchard located in eastern Spain during two seasons. Standardize critical soil water contents were: I) 24 % vol. for post-harvest, bloom - fruit set and phase III of fruit growth; II) 27 % vol. for phase I of fruit growth, and III) 29 % vol. for phase II of fruit growth with average daily air vapour pressure deficit values ranging between 0.2 - 0.4; 0.9–1.1 and 1.1–1.3 kPa, respectively. When implemented in the orchard, the sensor-based strategy resulted in water saving of 26 % respect to a control treatment, irrigated using the standard FAO-56 approach, without significant differences in yield and increasing the crop water productivity by 33 %. In conclusion, we suggest that the determination and use of the critical soil water content is a useful tool for scheduling irrigation. The proposed standardization and extrapolation methodology allows the irrigation strategy to be applied to other mandarin orchards under similar climatic conditions.